Impact of Targeting β3 Receptor on Male Sex Hormonal Balance - Ahmad, Abdulla; Saarti, Mohammed; Younes, Mohammed (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Sympathetic stimulation has a significant impact on the physiology and pathology of the male reproductive system. β3 receptor is suspected to play a role in the regulation of fertility status in men. AIM: The study aims to investigate the role of the β3 receptor in regulating the fertility parameters (testosterone, estrogen, progesterone, and histology of testis) in male rats. MATERIALS AND METHODS: Male albino rats have been given either placebo (controls) or β3 agonist (Mirabegron). Testosterone, estrogen, and progesterone are measured before and after treatment for all cases and controls. Histology of testis is investigated for all the rats as well. RESULTS: β3 receptor activation caused a significant increase in testosterone plasma concentration and a significant reduction in estrogen plasma concentration. β3 agonist did not affect the progesterone plasma concentration. Histological sections showed that β3 activation resulted in degeneration of the spermatocytes and accumulation of edema between the seminiferous tubules in the testis. CONCLUSION: β3 receptor has a potentially important role in the fertility status of male rats via regulating sex hormonal profile and altering the histology of the testis.